Obstacle Avoidance Strategy of Mobile Robot Based on Wireless Sensor Networks - An, Peng (International Journal of Online and Biomedical Engineering (iJOE), 2016)
In order to improve the real time performance, accuracy and stability, an obstacle avoidance strategy of mobile robot based on wireless sensor networks is proposed in this paper. The algorithm is combined with fuzzy control and neural network control theory which can express those rules difficult to describe by using mathematical model. Simulation results show that the obstacle avoidance strategy can improve the overall system performance substantially and is suitable for mobile robot intelligent control.